Spectral sensing research for surface and air monitoring in chemical, biological and radiological defense and security applications - Theriault, Jean-Marc, 1954-; Jensen, James O. (Selected topics in electronics and systems, 2009)
This book provides unique perspectives on the state of the art in multispectral/hyperspectral techniques for early-warning monitoring against chemical, biological and radiological (CB&R) contamination of both surface (e.g. land) and air (e.g. atmospheric) environments through the presentation of a comprehensive survey of the novel spectroscopic methodologies and technologies that are emerging to address the CB&R defense and security challenges of the future. The technical content in this book lends itself to the non-traditional requirements for point and stand-off detection that have evolved out of the US joint services programs over many years. In particular, the scientific and technological work presented seeks to enable hyperspectral-based sensing and monitoring that is in real time and in-line; low in cost and labor requirements; and easy to support, maintain and use in military and security-relevant scenarios.--Publisher's description.